Effects of Bisphenol-A on proliferation and expression of genes related to synthesis of polyamines, interferon tau and insulin-like growth factor 2 by ovine trophectoderm cells (2018)
This study evaluated the effects of bisphenol A (BPA) on proliferation of ovine trophectoderm (oTr1) cells, as well as expression of genes for transport of arginine and synthesis of polyamines. BPA reduced proliferation of oTr1 cells at concentrations of 1 × 10−6, 1 × 10−5, 1 × 10−4 M compared to concentrations of 0, 1 × 10−9, and 1 × 10−8 M at 24 and 96 h of culture. Lower concentrations of BPA significantly increased expression of mRNAs for agmatinase (AGMAT), arginine decarboxylase (ADC), ornithine decarboxylase (ODC1) and solute carrier family 7 member 1 (SLC7A1). Similarly, synthesis of polyamines by oTr1 cells was greatest at lower concentrations of BPA and decreased as the dose of BPA increased. Expression of mRNAs for interferon tau (IFNT) and insulin-like growth factor 2 (IGF2) by oTr1 cells was greater than for controls at 1 × 10−9 M BPA. Overall, the effects of BPA on proliferation and gene expression by oTr1 cells were highly dose-dependent.